Brucella lumazine synthase elicits a mixed Th1-Th2 immune response and reduces infection in mice challenged with Brucella abortus 544 independently of the adjuvant formulation used - Velikovsky, C.A. (2003)
The immunogenicity and protective efficacy of recombinant lumazine synthase from Brucella spp. (rBLS) administered with different adjuvants was evaluated in mice. Mice were immunized with rBLS in the absence or the presence of aluminum hydroxide gel (BLS-A1), monophosphoryl lipid A (BLS-MPA), or incomplete Freund's adjuvant (BLS-IFA). rBLS per se induced a vigorous immunoglobulin G (IgG) response, with high titers of IgG1 as well as IgG2. All the adjuvants increased this response; the BLS-IFA formulation was the most effective at inducing BLS-specific IgG antibodies. In addition, after in vitro stimulation with rBLS, spleen cells from BLS-IFA-, BLS-A1-, or BLS-MPA-immunized mice proliferated and produced interleukin-2 (IL-2), gamma interferon (IFN-γ), IL-10, and IL-4, suggesting the induction of a mixed Th1-Th2 response. Immunization with rBLS protected mice against challenge with B. abortus 544. The levels of protection in the spleen were similar for all adjuvants, but only BLS-A1 and BLS-IFA were effective in the liver. Our results indicate that BLS might be a useful candidate for the development of subunit vaccines against brucellosis, since it elicits antigen-specific cellular responses, with production of IFN-γ and protection, independently of the adjuvant formulation used.